(untitled) (Research, Society and Development, 2021)
Aspiration and ingestion of teeth, dental prostheses and other foreign bodies in maxillofacial injuries is a known complication necessitating prompt recognition and early treatment to minimize potentially serious and, sometimes, even fatal consequences. However, an aspirated or ingested foreign body does not always produce untoward affects and may be overlooked when no acute respiratory distress is evident or multiple life-threatening injuries are present. Here, we report a case in its presentation; the patient underwent extraction of a left upper third molar. After extraction, alveolar irrigation was performed with syringe, needle and sterile saline. the patient ingested the irrigation needle. The patient was properly referred to the emergency room of the hospital of Santa Fé do Sul and referred to the care of the general surgeon, who removed the needle with endoscopic removal under sedation. Clinicians must be aware that the instrument used for dental treatment are mostly small and there is a risk of these falling into the oropharynx and being swallowed or inhaled. The paper also emphasizes that attention to the potentially serious consequences and to offer guidance on management.